Macroeconomic policies in an interdependent world - Bryant, Ralph C.; Brookings Institution; International Monetary Fund.; Centre for Economic Policy Research (Great Britain) (Washington, D.C. : Brookings Institution, 1989)
Each essay in this book focuses on some aspect of international economic interdependence, and the book itself in the result of an international collaboration in the production and dissemination of economic research.
Papers from a conference held at the Brookings Institution in Dec. 1988, sponsored by the Institution, the International Monetary Fund, and the Centre for Economic Policy Research.
Includes bibliographical references.
ucj 17/01/2019
Loans
Keywords: Macroeconomics; Economic policy; International economic relations